A New Self-Conscious Turn at the Turn of the Centruy? - Tönnies, Merle (anglistik & englischunterricht)

Das viktorianische Theater als Populärkultur - Tönnies, Merle (Eine Kulturgeschichte der englischen Literatur: Von der Renaissance bis zur Gegenwart)

Hooper, B.: Voices in the Heart. Postcolonialism and Identity in Hong Kong Literature, 2003 - Tönnies, Merle (Anglistik)

Normal Mode Coupling in Photonic Crystal Nanocavities - Förstner, Jens; Dineen, Colm; Zakharian, A.R.; Moloney, Jerome V.; Koch, Stephan W. (Frontiers in Optics)
We numerically investigate strong light-matter interaction and normal mode coupling/splitting in a system composed of a single two-level atom and the localized mode of a small mode volume photonic crystal nanocavity.

Ultrafast electron-phonon interaction of intersubband transitions: Quantum kinetics from adiabatic following to Rabi-oscillations - Butscher, Stefan; Förstner, Jens; Waldmüller, Inès; Knorr, Andreas (Physical Review B)
The interaction of electrons with LO phonons provides an important mechanism of optical dephasing and carrier scattering for the two-dimensional electron gas in semiconductor quantum wells. In this paper, the corresponding ultrafast nonlinearities for off-resonant and resonant intersubband excitations are investigated. Quantum kinetic effects of the electron-phonon interaction and the corresponding violation of the microscopic energy conservation yield a qualitative different picture compared to the standard Markovian theory, if the phonon energy is larger than the intersubband-gap energy.
Keywords: tet_topic_qw

Quantum information processing using Coulomb-coupled quantum dots - Danckwerts, J.; Förstner, Jens; Knorr, A. (AIP Conference Proceedings)
A system of two quantum dots coupled by dipole‐dipole interaction is investigated within a density matrix approach. We compute the temporal evolution of the system in the linear and nonlinear optical regime and discuss the possibility of performing basic quantum information gates. The influence of the Förster energy transfer on Rabi oscillations is discussed.
Keywords: tet_topic_qd

Electromagnetic field structure and normal mode coupling in photonic crystal nanocavities - Dineen, C.; Förstner, Jens; Zakharian, A.R.; Moloney, J.V.; Koch, S.W. (Optics Express)
The electromagnetic field of a high-quality photonic crystal nanocavity is computed using the finite difference time domain method. It is shown that a separatrix occurs in the local energy flux discriminating between predominantly near and far field components. Placing a two-level atom into the cavity leads to characteristic field modifications and normalmode splitting in the transmission spectra.
Keywords: tet_topic_phc

Microscopic theory of electron dynamics and time-resolved two-color two-photon photoemission at semiconductor surfaces - Zeiser, A.; Bücking, N.; Förstner, Jens; Knorr, A. (Physical Review B)
A microscopic description based on the density matrix formalism is developed to describe the dynamics of photoemission of hot electrons at semiconductor surfaces, including the interaction of bulk and surface states. The equations of motion for the electronic occupations and transitions include the interaction with arbitrary optical fields as well as the electron-phonon coupling. Model wave functions are used to qualitatively describe the bulk-surface dynamics and the subsequent time resolved two-photon photoemission s2PPEd spectra. Our results suggest that it is possible to extract energetic and temporal information of the underlying dynamical occupations of the intermediate states from the 2PPE spectra.

Kinetic theory of the electron transport in the two photon photo emission at semiconductor surfaces - Bucking, N.; Zeiser, A.; Förstner, Jens; Knorr, A. (2005 Quantum Electronics and Laser Science Conference)
A theoretical description of ultrafast phonon induced electronic transport between surface and bulk states after optical excitation is presented. In particular, the influence of the electron transfer processes on two photon photo emission is evaluated.

Ultrafast quantum kinetics of semiconductor intersubband transitions: polaron signatures and dephasing dynamics - Butscher, S.; Förstner, Jens; Waldmuller, I.; Knorr, A. (2005 Quantum Electronics and Laser Science Conference)
The ultrafast intersubband dynamics in a semiconductor quantum well subband system is investigated theoretically. Non-Markovian electron-phonon interaction leads to polaron formation and enhanced dephasing.

Resonance fluorescence of semiconductor quantum dots: Signatures of the electron-phonon interaction - Ahn, K. J.; Förstner, Jens; Knorr, A. (Physical Review B)
Using a fully quantized description of strongly confined electrons interacting with acoustic phonons and the photon field, the nonstationary resonance-fluorescence spectra of a semiconductor quantum dot are investigated. For excitation pulses with durations approaching typical electron-phonon scattering times, the virtual quantum processes yield an observable electron-phonon sideband broadening.
Keywords: tet_topic_qd

Femtosecond Transfer Dynamics of Photogenerated Electrons at a Surface Resonance of Reconstructed InP(100) - Töben, L.; Gundlach, L.; Ernstorfer, R.; Eichberger, R.; Hannappel, T.; Willig, F.; Zeiser, A.; Förstner, Jens; Knorr, A.; Hahn, P. H.; Schmidt, W. G. (Physical Review Letters)
Time-dependent two-photon photoemission spectra are used to resolve the femtosecond dynamics of hot electrons at the energetically lowest surface resonance of reconstructed InP(100). Two different cases are studied, where electrons either are lifted into the surface resonance via a direct optical transition or are captured from bulk states. These data are the first of this kind recorded with a time resolution below 70 fs. The microscopic analysis shows that electron-phonon scattering is a major mechanism for electron transfer between surface and bulk states.

Phase Evolution of Solitonlike Optical Pulses during Excitonic Rabi Flopping in a Semiconductor - Nielsen, N. C.; zu Siederdissen, T. Höner; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Giessen, H. (Physical Review Letters)
We demonstrate that the temporal pulse phase remains essentially unaltered before separate phase characteristics are developed when propagating high-intensity pulses coherently on the exciton resonance of an optically thick semiconductor. This behavior is a clear manifestation of self-induced transmission and pulse breakup into solitonlike pulses due to Rabi flopping of the carrier density. Experiments using a novel fast-scan cross-correlation frequency-resolved optical gating (XFROG) method are in good agreement with numerical calculations based on the semiconductor Bloch equations.
Keywords: tet_topic_qd

Temporal and Spatial Pulse Compression in a Nonlinear Defocusing Material - Nielsen, N. C.; zu Höner Siederdissen, T.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Giessen, H. (Springer Series in Chemical Physics)
We investigate the spatiotemporal characteristics of subpicosecond pulse propagation in the nonlinear defocusing regime below the band edge of bulk GaAs. We observe temporal and spatial pulse compression and instabilities.
Keywords: tet_topic_polariton

Determinanten der Nachfrage nach Personaldienstleistungen durch Unternehmen - Überlegungen zur "strukturellen Stimmigkeit" der Personalarbeit - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Thommes, Kirsten (Strukturelle Stimmigkeit in der Betriebswirtschaftslehre)

Besonderheiten und Wettbewerbsprobleme des Marktes für wissenschaftliche Fachzeitschriften - Haucap, Justus; Hartwich, Tobias; Uhde, André (Vierteljahrshefte zur Wirtschaftsforschung)
ie Preise für wissenschaftliche, technische und medizinische (WTM) Fachzeitschriften sind in den letzten 20 Jahren dramatisch gestiegen. Die unterschiedlichen Preisentwicklungen zwischen kommerziellen und nichtkommerziellen Verlagen ist dabei nicht durch unterschiedliche Kostenentwicklungen zu erklären. Vielmehr haben die forschungsorientierten Top-Journale Marktmacht, da sie den Charakter positionaler Güter haben, die von Bibliotheken nur sehr schwer substituiert werden können, sodass streng genommen aufgrund der Einzigartigkeit jedes einzelnen Artikels jede Top-Zeitschrift einen eigenen Markt konstituiert. Top-Zeitschriften haben aus drei Gründen einen erheblichen Preissetzungsspielraum: Erstens sind der Markteintritt und die Ablösung teurer Top-Journale aufgrund des Koordinationsproblems zwischen Autoren, Gutachtern und Bibliotheken für neue Zeitschriften sehr schwierig. Zweitens haben Bibliotheken Wechselkosten (durch die Tendenz, vollständige Reihen zu beziehen). Drittens ist die Nachfrage auch aufgrund der kollektiven Entscheidungsfindung in Bibliotheken relativ unelastisch. Ein effektiver Ausweg, der die Verlage disziplinieren würde, könnte die konzertierte Aktion von Forschungsgemeinschaften sein, die ihre Mitarbeiter oder die von ihnen finanziell geförderten Wissenschaftler verpflichten, ihre Artikel und Forschungsergebnisse kostenfrei oder zumindest zu günstigen Konditionen zur Verfügung zu stellen.

Produktivitätsschocks und dynamische Optimierung - Broll, Udo; Gilroy, Bernard Michael; Lukas, Elmar (WiSt-Wirtschaftswissenschaftliches Studium)

The European 'No-Frills'-Aviation Market: Current and Future Developments - Gilroy, Bernard Michael; Lukas, Elmar; Volpert, Tobias (Competition versus Predation in Aviation Markets: A Survey of Experience in North America, Europe and Australia)

HRM in the German Business System: A Review. - Giardini, A; Kabst, Rüdiger; Müller-Camen, M (Management Revue: The International Review of Management Studies.)

Interim-Management: A Paradox for Leadership Research? - Bruns, J; Kabst, Rüdiger (Management Revue: The International Review of Management Studies.)

Vertrauen, Opportunismus, Kontrolle: Eine empirische Analyse von Joint Venture Beziehungen vor dem Hintergrund der Transaktionskostentheorie. - Eberl, P; Kabst, Rüdiger (Managementforschung.)

A honeypot for the exploration of spammers' behaviour - Schryen, Guido (IATAC IAnewsletter)

An e-mail honeypot addressing spammers' behavior in collecting and applying addresses - Schryen, Guido (Proceedings of the 6th IEEE Information Assurance Workshop)
Spam has become one of the most annoying and costly phenomenon in the Internet. Valid e-mail addresses belong to the most valuable resources of spammers, but little is known about spammers? behavior when collecting and harvesting addresses and spammers? capabilities and interest in carefully directed, consumer-oriented marketing have not been explored yet. Gaining insight into spammers? ways to obtain and (mis)use e-mail addresses is useful in many ways, e.g. for the assessment of the effectiveness of address obscuring techniques and the usability and necessity of hiding e-mail addresses on the Internet. This paper presents a spam honeypot project in progress addressing these issues by systematically placing e-mail addresses in the Internet and analyzing received e-mails. The honeypot?s conceptual framework, its implementation, and first empirical results are presented. Finally, an outlook on further work and activities is provided.
Keywords: Spam; ham; e-mail; honeypot; address obscuring technique; address taxonomy

Dynamic Load Balancing in Distributed Hash Tables - Bienkowski, Marcin; Korzeniowski, Miroslaw; Meyer auf der Heide, Friedhelm (Peer-to-Peer Systems IV)

Page Migration in Dynamic Networks - Bienkowski, Marcin; Meyer auf der Heide, Friedhelm (Mathematical Foundations of Computer Science 2005)

A Web Computing Environment for Parallel Algorithms in Java - Bonorden, Olaf; Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Proceeedings of 6th International Conference on Parallel Processing and Applied Mathematics (PPAM))
We present a web computing library (PUBWCL) in Java that allows to execute strongly coupled, massively parallel algorithms in the bulk-synchronous (BSP) style on PCs distributed over the internet whose owners are willing to donate their unused computation power. PUBWCL is realized as a peer-to-peer system and features migration and restoration of BSP processes executed on it. The use of Java guarantees a high level of security and makes PUBWCL platform independent. In order to estimate the loss of efficiency inherent in such a Java-based system, we have compared it to our C-based PUB-Library.

Load Balancing Strategies in a Web Computing Environment - Bonorden, Olaf; Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Proceeedings of 6th International Conference on Parallel Processing and Applied Mathematics (PPAM))
We compare different load balancing strategies for Bulk-Synchronous Parallel (BSP) programs in a web computing environment. In order to handle the influence of the fluctuating available computation power, we classify the external work load. We evaluate the load balancing algorithms using our web computing library for BSP programs in Java (PUBWCL). Thereby we simulated the external work load in order to have repeatable testing conditions. With the best performing load balancing strategy we could save 39% of the execution time averaged and even up to 50% in particular cases.

Towards Automated Chaos Verification - Day, Sarah; Junge, Oliver; Mischaikow, Konstantin (EQUADIFF 2003)

Transport in Dynamical Astronomy and Multibody Problems - Dellnitz, Michael; Junge, Oliver; Koon, Wang Sang; Lekien, Francois; Lo, Martin W.; Marsden, Jerrold E.; Padberg, Kathrin; Preis, Robert; Ross, Shane D.; Thiere, Bianca (International Journal of Bifurcation and Chaos)
We combine the techniques of almost invariant sets (using tree structured box elimination and graph partitioning algorithms) with invariant manifold and lobe dynamics techniques. The result is a new computational technique for computing key dynamical features, including almost invariant sets, resonance regions as well as transport rates and bottlenecks between regions in dynamical systems. This methodology can be applied to a variety of multibody problems, including those in molecular modeling, chemical reaction rates and dynamical astronomy. In this paper we focus on problems in dynamical astronomy to illustrate the power of the combination of these different numerical tools and their applicability. In particular, we compute transport rates between two resonance regions for the three-body system consisting of the Sun, Jupiter and a third body (such as an asteroid). These resonance regions are appropriate for certain comets and asteroids.

Transport of Mars-Crossing Asteroids from the Quasi-Hilda Region - Dellnitz, Michael; Junge, Oliver; Lo, Martin W.; Marsden, Jerrold E.; Padberg, Kathrin; Preis, Robert; Ross, Shane D.; Thiere, Bianca (Physical Review Letters)

A set oriented approach to optimal feedback stabilization - Grüne, Lars; Junge, Oliver (Systems & Control Letters)

A Survey of Methods for Computing (un)stable Manifolds of Vector Fields - Krauskopf, B.; Osinga, H. M.; Doedel, E. J.; Henderson, M. E.; Guckenheimer, J.; Vladimirsky, A.; Dellnitz, M.; Junge, O. (International Journal of Bifurcation and Chaos)
The computation of global invariant manifolds has seen renewed interest in recent years. We survey different approaches for computing a global stable or unstable manifold of a vector field, where we concentrate on the case of a two-dimensional manifold. All methods are illustrated with the same example — the two-dimensional stable manifold of the origin in the Lorenz system.

Satellite Formation, a Mobile Sensor Network in Space - Krishnamurthy, A.; Preis, R. (19th IEEE International Parallel and Distributed Processing Symposium)

Design and implementation of a hybrid energy supply system for railway vehicles - Li, R.; Pottharst, A.; Frohieke, N.; Becker, J.; Witting, K.; Dellnitz, M.; Znamenshchykov, O.; Feldmann, R. (Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005.)

Aktuelle Entwicklung im europäischen Bank- und Kapitalmarktrecht - Krimphove, Dieter (Zeitschrift für das gesamte Kreditwesen)

Covering Pareto Sets by Multilevel Subdivision Techniques - Dellnitz, M.; Schtze, O.; Hestermeyer, T. (Journal of Optimization Theory and Applications)

Regulierung und Haftung von Ratingagenturen: Status quo und Perspektiven - Krimphove, Dieter; Kruse, Oliver (Zeitschrift für das gesamte Kreditwesen)

Rechts- und Haftungsfragen des externen Unternehmensratings - Krimphove, Dieter (Finanz Betrieb)

ARIDA - Eine Abstraktion von Eingabegeräten zur Verwendung in augmented Reality Anwendungen, Virtuelle und Erweiterte Realität - Redmer, B.; Goetz, F.; Domik, Gitta

Integration of Point Based Rendering into a Common Scene Graph System - Goetz, F.; Hillebrand, L.; Domik, Gitta (the 5th IASTED International Conference on Visualization, Imaging, and Image Processing)

Towards automized chaos verification - Day, Sarah; Junge, Oliver; Mischaikow, Konstantin (Proceedings of Equadiff 2003, International Conference on Differential Equations)

Average case complexity of Voronoi diagrams of n sites from the unit cube - Bienkowski, Marcin; Damerow, Valentina; Meyer auf der Heide, Friedhelm; Sohler, Christian (Proceedings of the 21st European Workshop on Computational Geometry, Eindhoven, The Netherlands, March 9-11, 2005)

Abstracts Collection -- Algorithmic Aspects of Large and Complex Networks

Adaptive Filter-and-Sum Beamforming in Spatially Correlated Noise - Haeb-Umbach, Reinhold; Warsitz, Ernst (International Workshop on Acoustic Echo and Noise Control (IWAENC 2005))
In this paper we propose a novel adaptation algorithm for Filter-and-Sum beamforming in spatially correlated noise. Deterministic and stochastic gradient ascent algorithms are derived from a constrained optimization problem, which iteratively estimate the principal eigenvecto r of a generalized eigenvalue problem. The method does not require an explicit estimation of the speaker location. It is shown that the well-known Delay-and-Sum beamformer and the previously introduced Filter-and-Sum beamformer in spatially white noise are obtained as special cases. Further, bounds on the maximally achievable SNR gains are derived and it is shown that the proposed adaptation algorithm is able to approach these performance bounds.

A Unified Probabilistic Approach to Error Concealment for Distributed Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (Interspeech 2005)
The transmission errors in a wireless or packet oriented network may dramatically decrease the performance of a distributed speech recognition DSR) system. Error concealment has been shown to be an effective way to mantain an acceptable word error rate when dealing with error prone communication channels. In this paper we propose an extension of our previously introduced soft features approach for the case that the soft-output of the channel decoder is not available at the server side of the DSR system. We found a simple method to estimate bit reliability information which still gives good speech recognition results. It is shown that some other error concealment schemes turn out to be special cases of the method proposed here.

A Comparison of Soft-Feature Distributed Speech Recognition with Candidate Codecs for Speech Enabled Mobile Services - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2005))
In this paper we present a comparison of the recently proposed Soft-Feature Distributed Speech Recognition (SFDSR) with the two evaluated candidate codecs for Speech Enabled Services over wireless networks: Adaptive Multirate Codec (AMR) and the ETSI Extended Advanced Front-End for Distributed Speech Recognition (XAFE). It is shown that SFDSR achieves the best recognition performance on a simulated GSM transmission, followed by XAFE and AMR.We also present some new results concerning SFDSR which demonstrate the versatility of the approach. Further, a simple method is introduced which considerably reduces the computational effort.
Keywords: adaptive codes; adaptive multirate codec; AMR; distributed speech recognition; ETSI; extended advanced front-end; recognition performance; SFDSR; simulated GSM transmission; soft-feature distributed speech recognition; speech codecs; speech coding; speech recognition; variable rate codes; XAFE

Acoustic filter-and-sum beamforming by adaptive principal component analysis - Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2005))
For human-machine interfaces in distant-talking environments multichannel signal processing is often employed to obtain an enhanced signal for subsequent processing. In this paper we propose a novel adaptation algorithm for a filter-and-sum beamformer to adjust the coefficients of FIR filters to changing acoustic room impulses, e.g. due to speaker movement. A deterministic and a stochastic gradient ascent algorithm are derived from a constrained optimization problem, which iteratively estimates the eigenvector corresponding to the largest eigenvalue of the cross power spectral density of the microphone signals. The method does not require an explicit estimation of the speaker location. The experimental results show fast adaptation and excellent robustness of the proposed algorithm.
Keywords: acoustic filter-and-sum beamforming; acoustic room impulses; acoustic signal processing; adaptive principal component analysis; adaptive signal processing; architectural acoustics; constrained optimization problem; cross power spectral density; deterministic algorithm; deterministic algorithms; distant-talking environments; eigenvalues and eigenfunctions; eigenvector; enhanced signal; filter-and-sum beamformer; FIR filter coefficients; FIR filter coefficients; FIR filters; gradient methods; human-machine interfaces; iterative estimation; iterative methods; largest eigenvalue; microphone signals; multichannel signal processing; optimisation; principal component analysis; spectral analysis; stochastic gradient ascent algorithm; stochastic processes

Bestimmung des Anteils ungelöster Gase in flüssigen Medien - Gulsch, Michael; Henning, Bernd
Impulsbasierte Ultraschallsensorsysteme zur Messung von Füllstand, Durchfluss und Konzentration sind heutzutage aufgrund ihrer Robustheit und Wartungsfreundlichkeit weit verbreitet. Probleme treten immer dann auf, wenn sich Gasblasen im Medium befinden. Diese verändern das empfangene Signal derart, dass eine exakte Messung der Schallgeschwindigkeit des flüssigen Mediums nicht mehr möglich ist. Dieser Beitrag behandelt eine neue Art der Signalauswertung, die eine zuverlässige Bestimmung der Schallgeschwindigkeit auch in diesem Fall gewährleistet. Darüber hinaus können auch Rückschlüsse auf den Gasanteil innerhalb des flüssigen Mediums gewonnen werden.

Bubble detection and gas volume measurement in bubble loaded liquids with pulse driven measurement devices - Gulsch, Michael; Henning, Bernd (2005 IEEE Ultrasonics Symposium)
Currently there are pulse based ultrasonic sensor systems used to measure flow, liquid level, concentration or in process monitoring. In several processes the investigated media are a mixture of liquid and solid ingredients (emulsions, suspensions). The use of ultrasonic sensor systems will be very complicated if gas bubbles appear at the measurement place caused by chemical reactions, high temperature or fast flow that means by typical process conditions. Firstly, the appearance of gas bubbles falsifies the measured absorption. Secondly, the measured velocity is influenced by gas bubbles. In figure 1 is visible that a volume fraction of 0.1 ppm of undissolved air decreases the sound velocity by 1.4 m s-1

Gasvolumenmessung in blasenbeladenen Flüssigkeiten - Gulsch, Michael; Henning, Bernd (Fortschritte der Akustik - DAGA '05)
In vielen verfahrenstechnischen Prozessen ist die kontinuierliche Regelung von Prozessgrößen für einen stabilen und sicheren Betrieb eine wichtige Vorraussetzung. Die Erfassung der Zielgrößen geschieht aufgrund von hoher Robustheit und Wartungsfreundlichkeit zunehmend mit akustischen Messverfahren. Besonders impulsbasierte Messsysteme werden häufig zur Messung von Durchfluss, Füllstand und in der Flüssigkeitsanalytik auch zur Konzentrationsmessung benutzt. Dabei führen am Messort auftretende Gasblasen zu großen messtechnischen Problemen. Sie verändern die gemessenen akustischen Stoffkenngrößen, wodurch es zur fehlerhaften Regelung bestimmter Prozesszielgrößen kommt.

Visualisation and Measurement of Condensed Water in Automobile Headlights - Gulsch, Michael; Unverzagt, Carsten; Henning, Bernd; Nolte, Sascha
Today headlights are built with transparent polycarbonate front windows. If the air moisture inside the headlight is high and the outside temperature decreases below the dew-point, the air moisture condensates inside and the inner surface of the polycarbonate front window (PCFW) becomes nontransparent (figure 1). To the costumer this appears as an optical defect.In order to avoid the condensation and to speed up the evaporation of the condensed water (condensate) on the PCFW a Computational-Fluid-Dynamic-simulation is used. The simulation results are proceeded to optimise the airflow and the arrangement of the breather holes. An important problem is the validation of the simulated results with the reality. It was necessary to build a non-invasive measurement system for the continuous characterisation of condensated areas without affecting the material properties, the airflow and the light distribution inside the headlight.

Quantum 1/f Effect in Resonant Biochemical Piezoelectric and MEMS Sensors - Handel, Peter; Tournier, Adam; Henning, Bernd (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Acoustic properties of highly attenuating isotropic media - Rautenberg, Jens; Henning, Bernd
In the 1950's many investigations have been made in measuring the Young's and the shear modus of isotropic materials with acoustic waves. Therefore both the longitudinal and transversal sound velocities have been determined with only one specimen, that had to be large in comparison to the wavelength (Brown, Reynolds, Dunegan). Therewith the method was suited only for low absorbing materials. In the 1990's further developments led to mono mode rods to describe viscoelastic properties. Their diameters had to be very small for high frequencies, thus giving practical values up to 65 kHz (Benatar). This contribution is about a tubular multi mode specimen and its application for the simultaneous measurement of the abovementioned acoustic properties at high frequencies.

Charakterisierung einzelner Ultraschallwandler für den Aufbau eines mehrelementigen parametrischen Lautsprechers - Rautenberg, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA '05)
In den bekannten grundlegenden Ausf¨uhrungen zur Erzeugung hörbaren Schalls durch Eigendemodulation amplitudenmodulierten Leistungsultraschalls (siehe u.a. Westervelt, Berktay) wird von zwei räumlich übereinander liegenden Wellen unterschiedlicher Frequenz im nichtlinearen Medium ausgegangen, so dass neben ihren Harmonischen auch Summen- und Differenzfrequenzen entstehen. Die perfekte räumliche Ueberdeckung der Wellen im Freifeld kann mit herkömmlichen Schallwandlern allerdings nur unzul¨anglich erreicht werden. Trotzdem sind in der Vergangenheit einige so genannte parametrische Lautsprecher entwickelt worden. Um annähernd die erwähnten Voraussetzungen zu gewährleisten, sind gängige Systeme mit einem Durchmesser von ca. 30 cm relativ groß. Dies soll auch dem angestrebten Sekundärschalldruck Rechnung tragen, der linear mit der effektiv abstrahlenden Fl¨ache wächst. Zum Aufbau dieser großen Flächen werden teilweise viele kleine Ultraschallwandler zu einem Array zusammengesetzt. Der hohe Preis einzelner Wandler aber auch die notwendige Sortierung beispielsweise bezüglich ihrer Mittenfrequenz macht den Aufbau solcher Systeme aufwändig. Erst am vollständig aufgebauten Array werden schließlich Frequenzgang und Richtcharakteristik des Sekundärschalls ermittelt. Im Sinne kürzerer Entwicklungszeiten und -kosten wäre es wünschenswert, bereits vor dem Aufbau des Arrays allein durch Untersuchung des einzelnen Ultraschallwandlers eine Prognose über die zu erwartenden Eigenschaften des Gesamtsystems vornehmen zu können. In diesem Beitrag wird ein Versuchsaufbau vorgestellt, der unter strenger Beachtung der anfangs erwähnten Voraussetzungen die parametrische Schallerzeugung mit nur einem Ultraschallwandler kleiner Baugröße erlaubt. Die Frequenzg änge des Sekundärschalls von Einzelelement und Array werden bei entsprechender Distanz gegen¨ubergestellt. Vorzüge des neuen Messaufbaus, beispielsweise die Möglichkeit zur Variation von Druck, Temperatur oder Luftfeuchtigkeit, um atmosphärische Einflüsse auf die parametrische Schallerzeugung zu untersuchen, werden skizziert

Lower Frequency Bound of Parametric Arrays - Rautenberg, Jens; Henning, Bernd
One method to generate focused sound is to transmit amplitude modulated ultrasound of high energy in a nonlinear medium, so that sum and difference frequencies develop. Practically wide arrays of many small ultrasonic transducers are used, but the generation of very low frequencies is always weak. This contribution is about the experimental investigation of the {\textquotedbl}generation zone{\textquotedbl} -- that is the distance between the ultrasonic loudspeaker and the listener -- and the decrease of the lower frequency bound of the audible sound beam with distance. The main focus is on the experimental setup, which permits the parametric sound generation with only one ultrasonic transducer and a waveguide. In addition, the new measurement setup enables to show an additional effect: The de-coherence of the primary ultrasound wave which may be caused by saturation of air. This is why the lower frequency bound decreases as well if we approach the ultrasonic transducer.

Novices' expectations and prior knowledge of software development: results of a study with high school students - Schulte, Carsten; Magenheim, Johannes (ICER)

Beiträge der Objektorientierung zu einem Kompetenzmodell des informatischen Modellierens - Brinda, Torsten; Schulte, Carsten (INFOS)

Erwartungen und Wahlverhalten von Schülerinnen und Schülern gegenüber dem Schulfach Informatik - Ergebnisse einer Umfrage - Schulte, Carsten; Magenheim, Johannes (INFOS)

Calibrated label-ranking - Brinker, K.; Hüllermeier, Eyke (In Proceedings of the NIPS-2005 Workshop on Learning to Rank, Whistler, BC, Canada)

On position error and label ranking through iterated choice - Hüllermeier, Eyke; Fürnkranz, J.; Beringer, J. (In Proceedings LWA/FGML-2005, German Workshop on Machine Learning, Saarbrücken, Germany)

Polariton propagation in shallow-confinement heterostructures: Microscopic theory and experiment showing the breakdown of the dead-layer concept - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Rückmann, H. I.; Gutowski, J.; Gust, A.; Alexe, G.; Hommel, D. (Physical Review B)

Coherent propagation of polaritons in semiconductor heterostructures: Nonlinear pulse transmission in theory and experiment - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Wischmeier, L.; Rückmann, I.; Voss, T.; Gutowski, J.; Gust, A.; Hommel, D. (Physical Review B)

A method for combining interacting pieces of evidence in case-based learning - Hüllermeier, Eyke; NN, Cho-k (in Proceedings IJCAI-05, 19th international Joint Conference on Artificial Intelligence, Edingburgh, Scotland)

Learning label preferences: Ranking error versus position error - Hüllermeier, Eyke; Fürnkranz, J. (In Proceedings IDA-2005, 6th International Symposium on Intelligent Data Analysis, Madrid)

Learning from ambiguously labeled examples - Hüllermeier, Eyke; Beringer, J. (In Proceedings IDA-2005, 6th International Symposium on Intelligent Data Analysis, Madrid)

Verbessern Tax-Master- und WP-Master-Studiengänge die Ausbildungsqualität von Steuerberatern und Wirtschaftsprüfern? - Bareis, Peter; Hachmeister, Dirk; Kahle, Holger; Kiesewetter, Dirk; König, Rolf; Maiterth, Ralf; Niemann, Rainer; Rückle, Dieter; Schneider, Dieter; Siegel, Theodor; Sureth-Sloane, Caren; Treisch, Corinna (Zeitschrift für Steuern und Recht)

Auswirkungen der Vermögensteuer als Mindeststeuer auf die Investitionstätigkeit und die Attraktivität Deutschlands im internationalen Standortwettbewerb - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Wiedereinführung der Vermögensteuer als Mindeststeuer in Deutschland - Unlösbare Probleme bei der Bewertung von Grundbesitz und Unternehmen - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Vermögensteuer, Verluste und Investitionsentscheidungen - Sureth-Sloane, Caren (ForschungsForum Paderborn)

Capital Gains Taxation under Different Tax Regimes - Sureth-Sloane, Caren; Langeleh, Dirk

Wealth Tax As Alternative Minimum Tax? - The Impact of a Wealth Tax on Business Structure and Strategy - Sureth-Sloane, Caren; Maiterth, Ralf

Investitionsbereitschaft und zeitliche Indifferenz bei Realinvestitionen unter Unsicherheit und Steuern - Sureth-Sloane, Caren; Voß, Armin

Vererben und Verschenken von US-amerikanischem, französischem und österreichischem unternehmerischen Vermögen - eine steuersystematische Analyse sowie daraus abgeleitete Gestaltungsansätze - Tanto, Olaf

Stability versus speed in a computable algebraic model - Ziegler, Martin (Theoretical Computer Science)

A notion of comarative probabilistic entroy based on the possibilistic specificity ordering - Dubois, D.; Hüllermeier, Eyke (in Proceedings ECSQARU-2005, 8th European Conference of Symbolic and Quantitative Approaches to Reasoning with Uncertainty, Barcelona, Spain)

Adaptive XML Access Control Based on Query Nesting, Modification and Simplification - Böttcher, Stefan; Steinmetz, Rita (Datenbanksysteme in Business, Technologie und Web, 11. Fachtagung des GI-Fachbereichs "Datenbanken und Informationssysteme" (DBIS))

Embedding XML Schema Constraints in Search-Based Intersection Tests for XPath Query Optimization - Böttcher, Stefan; Steinmetz, Rita (16th International Workshop on Database and Expert Systems Applications (DEXA'05))

Detecting Privacy Violations in Sensitive XML Databases - Böttcher, Stefan; Steinmetz, Rita (Secure Data Management, Second VLDB Workshop, SDM 2005)

A fuzzy-probablistic risk assessment system for natural disasters - Karimi, I.; Hüllermeier, Eyke (in Proceedings IFSA-2005, 11th World Congress of the International Fuzzy System Association, Beijing, China)

Improving the interpretability of data-driven evolving fuzzy systems - Lughofer, E.; Hüllermeier, Eyke; Klement, E. (in Proceedings EUSFLAT-2005 4th International Conference on the European Society for Fuzzy Logic and Technology, Barcelona, Spain)

Learning complexity-boundet rule-based classifiers by combining association analysis and genetic algorithms - Yi, Y.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2005 4th International Conference on the European Society for Fuzzy Logic and Technology, Barcelona, Spain)

Fuzzy sets in machine learning and data mining: Status and prospects - Hüllermeier, Eyke (Fuzzy Sets and Systems)

Experience-based decision making: A satisficing decision tree approach - Hüllermeier, Eyke (IEEE Transactions on Systems, Man and Cybernetics-Part A: Systems and Humans)

Clustering of gene expression data using a local shape-based similarity measure - Balasubramaniyan, R.; Hüllermeier, Eyke; Weskamp, N.; Kämper, J. (Bioinformatics)

HGB: Basiswissen einschließlich Wechsel- und Scheckrecht Fälle und Lösungen auf interaktiver CD - Krimphove, Dieter

A Low Power Design for Embedded DRAMs with Online Consistency Checking - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

Dynamic Routing: A Prerequisite for Reliable NoCs - Ali, Muhammad; Welzl, Michael; Hellebrand, Sybille
Keywords: WORKSHOP

Power Consumption Versus Error Correcting Capabilities in Embedded DRAMs - A Case Study - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

The use of instant messaging in working relationship development: A case study - Trier, Matthias; Cho, Hee-Kyung; Kim, Eunhee (Journal of Computer-Mediated Communication)

IT-gestützte Modellierung und Analyse elektronischer Expertengemeinschaften (Modeling and Evaluation of Electronic Expert Communities) - Trier, Matthias (i-com)

Process-Oriented Production of Learning Units for Sustainable E-Learning Offerings - Müller, Claudia; Trier, Matthias; Herzog, Michael A. (E-Learning)

A Tool for IT-supported Visualization and Analysis of Virtual Communication Networks in Knowledge Communities - Trier, Matthias (Wirtschaftsinformatik 2005)

A Procedural Model for the Production of Reusable and Standard-Compliant E-Learning Offerings - Müller, Claudia; Trier, Matthias (Wirtschaftsinformatik 2005)

IT-Supported Visualization of Knowledge Community Structures - Trier, Matthias (Proceedings of the 38th Annual Hawaii International Conference on System Sciences)

Netzwerkorientiertes Wissensmanagement und seine Unterstützung durch Softwarewerkzeuge - Krallmann, Hermann; Trier, Matthias (Strategisches Wertschöpfungsmanagement in dynamischer Umwelt: Festschrift für Erich Zahn)

Adaptive scheduling for heterogeneous traffic flows in cellular wireless OFDM-FDMA systems - Valentin, Stefan; Gross, James; Karl, Holger; Wolisz, Adam (10th IFIP International Conference on Personal Wireless Communications/PWC'05, Comar, France, 2005)

Periodic real-time scheduling for FPGA computers - Danne, Klaus; Platzner, Marco (Proceedings of the Third International Workshop on Intelligent Solutions in Embedded Systems (WISES))

Memory-demanding Periodic Real-time Applications on FPGA Computers - Danne, Klaus; Platzner, Marco (Work-in-Progress Proceedings of the 17th Euromicro Conference on Real-time Systems (ECRTS))

A heuristic approach to schedule periodic real-time tasks on reconfigurable hardware - Danne, Klaus; Platzner, Marco (Proceedings of the 15th International Conference on Field Programmable Logic and Applications (FPL))

Quasiparticle bands and optical spectra of highly ionic crystals: AlN and NaCl - Bechstedt, F.; Seino, K.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)